The prevalence of maternal depression and its sociodemographic determinant in Selangor - Siregar, Pinta Pudiyanti; Sutan, Rosnah; Nasreen, Hashima E; Baharudin, Azlin (2017)
Introduction: Maternal depression and anxiety disorders are reported as current public health issues globally. The depressive or anxiety state will progressing worsen and risky to mother and foetal health as drastic hormonal changes occur following conception if no proper adjustment made. This study aims to investigate the prevalence of mother's depression and anxiety in Selangor and its demographic factors. Methodology: A baseline study was conducted in Selangor and the samples were recruited randomly. There were 461 mothers with 28 weeks of pregnancy (antenatal period) participated from 4 public health clinics: Shah Alam, Selayang, Kajang and Sungai Chua. Data collection was collected using validated self-administered questionnaire form which was available for both languages Malay or English. Assessment on the risk of depression was made using the Edinburgh Depression Scale (EPDS). Results: The prevalence of perinatal depression was 12.3% in Selangor with the cut of point of 12 for total score of EPDS. The only significant socio demographic factor found in present study was the employment status of the mother. Employed mothers (9.7%) had less prevalence risk of depression compared to higher prevalence noted among the unemployed mothers (16.9%, p< 0.05). Other socio-demographic factors were not found significant. Conclusions: Routine antenatal maternal depression screening is crucial to prevent deteriorating of health of mother and foetal. Early identification and appropriate management of underlying problems related will lead to better maternal outcomes. Spending more time to unemployed mothers may alleviate stress that lead to depressive or anxiety risk which can be done at public health clinics by trained personnel in counselling.